Optimasi Sistem Pembelajaran Pada Sistem E-Learning di Universitas Dharma Andalas melalui Pendekatan Kerangka Kerja ITIL V. 3 - Sularno; Dio Prima Mulya; Putri Anggraini; Suandi Daulay (Sekolah Tinggi Teknologi Pekanbaru, 2025)
The implementation of the e-learning system at Dharma Andalas University faces significant challenges in terms of an uninspiring user interface (UI), hindering the student learning experience. The main problems include complicated navigation, inconsistent visual design, and limited accessibility, making it difficult for students to make optimal use of the system. This research aims to optimize the e-learning UI system at Dharma Andalas University using the ITIL v3 framework. Research methods include analyzing user needs through interviews, surveys and direct observation. ITIL v3 stages, including Service Strategy, Service Design, Service Transition, Service Operation, and Continual Service Improvement (CSI), are applied to identify problems, design solutions, and make continuous improvements. A waterfall approach is used in development systems, ensuring a systematic workflow and focus on user needs. The research results show that interface optimization using ITIL v3 increases user satisfaction levels by up to 25%, with a reduction in task completion time by 30%. An optimized system is more responsive, easy to access across devices, and supports a more interactive learning experience. This research makes a significant contribution in managing IT-based e-learning services, especially in integrating the ITIL v3 approach to improve the quality of digital education at Dharma Andalas University.